The global economic crisis: Impact on India and policy responses - Rajiv Kumar; Pankaj Vashisht (Asian Development Bank Institute (ADBI), 2009)
India's financial sector is not deeply integrated with the global financial system, which spared it the first round adverse effects of the global financial crisis and left Indian banks mostly unaffected. However, as the financial crisis morphed in to a full-blown global economic downturn, India could not escape the second round effects. The global crisis has affected India through three distinct channels: financial markets, trade flows, and exchange rates. The reversal in capital inflows, which created a credit crunch in domestic markets along with a severe deterioration in export demand, contributed to the decline of gross domestic product by more than 2 percentage points in the fiscal year 2008-2009. In line with efforts taken by governments and central banks all over the world, the Government and the Reserve Bank of India took aggressive countercyclical measures, sharply relaxing monetary policy and introducing a fiscal stimulus to boost domestic demand. However, this paper argues that with very limited fiscal maneuverability and the limited traction of monetary policy, policy measures to restore the Indian gross domestic product growth back to its potential rate of 8-9% must focus on addressing the structural constraints that are holding down private investment demand.
Keywords: G01; E66; 330